2014
DOI: 10.1186/1472-6750-14-72
|View full text |Cite
|
Sign up to set email alerts
|

The avian cell line AGE1.CR.pIX characterized by metabolic flux analysis

Abstract: BackgroundIn human vaccine manufacturing some pathogens such as Modified Vaccinia Virus Ankara, measles, mumps virus as well as influenza viruses are still produced on primary material derived from embryonated chicken eggs. Processes depending on primary cell culture, however, are difficult to adapt to modern vaccine production. Therefore, we derived previously a continuous suspension cell line, AGE1.CR.pIX, from muscovy duck and established chemically-defined media for virus propagation.ResultsTo better under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…Interestingly, even after glutamine depletion, glutamate still accumulated. This phenomenon is not uncommon cell cultivations as glutamate is a nonessential amino acid and it is also produced from sources other than glutamine, for example, through lysine and proline catabolism (Lohr et al, 2014; Sonnewald, 2014). Although extracellular amino acids were not quantified in these experiments, batch cultivations with a similar medium composition performed for this cell line demonstrated that most amino acids were not depleted at the end of exponential cell growth phase (Priesnitz et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, even after glutamine depletion, glutamate still accumulated. This phenomenon is not uncommon cell cultivations as glutamate is a nonessential amino acid and it is also produced from sources other than glutamine, for example, through lysine and proline catabolism (Lohr et al, 2014; Sonnewald, 2014). Although extracellular amino acids were not quantified in these experiments, batch cultivations with a similar medium composition performed for this cell line demonstrated that most amino acids were not depleted at the end of exponential cell growth phase (Priesnitz et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…4B and D). Also, it has been reported that glutamine plays a minor role in energy supply for CR.pIX cells and that its absence might not influence the propagation of MVA in this cell line [29]. Therefore, the positive effect of a medium exchange at TOI on virus propagation might be also due to the dilution of inhibitory metabolites or signaling molecules rather than just a better supply of substrates.…”
Section: Effect Of Medium Exchanges At Time Of Infection On Virus Yieldsmentioning
confidence: 88%
“…Feeding was based on a constant cell-specific perfusion rate (CSPR) [27] taking into account the steady state mass balance for substrates as described by Kompala and Ozturk [28] with glucose as the major energy source for CR.pIX cells [29] as:…”
Section: Cultivation In Bioreactormentioning
confidence: 99%
“…In the variant called AGE1.CR.pIX, the human adenovirus serotype 5 structural gene pIX is additionally added to increase possible virus titers by the action of the pIX protein [55]. The cells were grown in suspension first in serum‐free medium, and later in CDM [56], reaching up to 9×10 6 cells/mL in batch mode [57]. Cell numbers of up to 5×10 7 cells/mL in this CDM in perfusion have recently been reached [34, 35].…”
Section: Currently Available “Designer Cell Lines”mentioning
confidence: 99%